Evaluation of neuroprotective effects of alpha-tocopherol in cuprizone-induced demyelination model of multiple sclerosis - Nilesh Kumar Mitra; Kong Yu Xuan; Charmaine Caryn Teo; Ng Xian-Zhuang; Anudeep Singh; Jestin Chellian (Wolters Kluwer Medknow Publications, 2020)
Background and Purpose: Multiple sclerosis (MS) is an autoimmune disorder characterized by demyelination and axonal loss. Quantitative estimation of behavioral, locomotor, and histological changes following the use of alpha-tocopherol (AT) in the animal model of MS have not been reported. The present study was planned to evaluate whether AT can improve sensorimotor dysfunction and reduce demyelination in the cuprizone (CPZ)-induced rat model of MS. Experimental approach: Female Sprague-Dawley rats (8 weeks) were fed with cuprizone diet for 5 weeks followed by intraperitoneal injections of alpha-tocopherol (100 mg/Kg) or PBS for 2 weeks (groups E1 and E2, n = 8). Group C (n = 8) was fed with normal pellets followed by intraperitoneal doses of PBS. Open-field test and beam walking were carried out on every 10th day. The mean area of demyelination in the corpus callosum was quantified in Luxol® fast blue (LFB) stained histological sections of the forebrain. Qualitative grading for relative changes in the stains of myelinated fibers was also done. Findings/Results: During withdrawal of CPZ, AT treatment increased the average speed by 22% in group E1, compared to group E2 (P < 0.05). The mean time to walk the beam was reduced in group E1 by 2.6% compared to group E2 (P < 0.05). The rearing frequency was increased in group E1 during week 6-7 compared to that in the period of CPZ treatment. The mean area of demyelination in the corpus callosum showed a 12% reduction in group E1 compared to group E2 (P < 0.05). Conclusion and implications: Short-term AT therapy showed improvement in motor dysfunction and reduction of demyelination in the animal model of MS.